Assessment of soil bacterial communities on Alexander Island (in the maritime and continental Antarctic transitional zone) - Chong, C.W.; Convey, P.; Pearce, D.A.; Tan, I.K.P. (2012)
Despite an increasing number of Antarctic soil diversity assessments, understanding of the bacterial community composition in the arid soil environments of the maritime/continental Antarctic transitional zone remains lacking. Most documented microbiological studies had focused on either the wetter environments of the Antarctic Peninsula/Scotia arc or the exceptionally arid deserts of the Dry Valleys of continental Antarctica. In this study, soil bacterial diversity from three relatively arid sites on Alexander Island and the physicochemical parameters that might inXuence it were assessed. In general, the study sites exhibited levels of pH, hydration and metal content different from previous reports of maritime or continental Antarctic soil habitats. Although the soil from Alexander Island exhibited similar phylum-level bacterial taxonomic composition to those of other cold and arid environments, each study site was found to harbour significantly different bacterial assemblages. The latter finding was supported by three complementary molecular methods selected to address different elements of diversity. Our analyses of the measured parameters suggest that the differences in bacterial communities were best explained by soil pH and copper content. Using these data, we suggest that soil pH might play an important role in structuring bacterial assemblage patterns across polar soils.